The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1516-80342012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Dores corporais em teleoperadores e sua relação com o uso da voz em atividades laborais

Abstract: Body aches in call center operators and the relationship with voice use during work activities Dores corporais em teleoperadores e sua relação com o uso da voz em atividades laboraisABSTRACT Purpose: To characterize types of body aches presented by call center operators and to verify the relationship of the selected body aches with voice use in work activities. Methods: 235 call center operators and 235 individuals from the general population responded to a questionnaire with closed questions about body aches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
8
0
3
Order By: Relevance
“…Participants of the present research are predominantly men with mean age close to the end of vocal efficiency period and working time in the occupation greater than that found in the literature (11,14,18) . This fact is justified because all participants of this study were civil servants: firefighters, military or civil police officers -professions with higher prevalence of men (20) .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Participants of the present research are predominantly men with mean age close to the end of vocal efficiency period and working time in the occupation greater than that found in the literature (11,14,18) . This fact is justified because all participants of this study were civil servants: firefighters, military or civil police officers -professions with higher prevalence of men (20) .…”
Section: Discussionmentioning
confidence: 85%
“…To this end, companies and public agencies which have a responsible policy of health promotion programs should invest in the prevention of diseases and provide assistance to these operators with the aid of an interdisciplinary team of professionals; this is an important tool for promoting quality of life and improving professional performance (1,10,14,24) . It is essential to prepare these workers to become the main agents in the proposal of changes to the vocal, environmental and organizational conditions of work (18,30) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain related to phonation among professionals who work with their voices has also been recently studied among teachers (15) , lyrical singers (19) , teleoperators (20) , and popular singers (21) . However, only a few studies explored this question, considering functional or organofunctional dysphonia, to investigate the presence of pain and its characteristic, related to phonation or not.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between body ache and vocal use has been approached in studies with voice professional and popular singers, focusing on the pain that are near the region of the larynx, throat pain, neck pain and pain while speaking 25,26 . Table 1 showed that the subjects' perception regarding voice changes during or after the performance are varied and involve functional aspects of voice production, discomforts and a great occurrence of aspects related to self-perception and auditory parameters, linked to disorders in voice quality such as hoarseness, voice breaks, loss of high notes and lower voice.…”
mentioning
confidence: 99%